3D Janus structure MXene/cellulose nanofibers/luffa aerogels with superb mechanical strength and high-efficiency desalination for solar-driven interfacial evaporation - Wang, Pei-Lin; Zhang, Wei; Yuan, Qi; Mai, Tian; Qi, Meng-Yu; Ma, Ming-Guo (Journal of colloid and interface science, 2023)
Janus MXene-decorated CNFs/luffa (JMCL) aerogel integrated the multifunction of fast water transport, good thermal management, fast vapor escape, and efficient photothermal conversion in a single-module. The hydrophobic lower part and hydrophilic upper part perform complementary functions, endowing the JMCL aerogel with high sunlight-to-heat-to-vapor conversion efficiency and self-floating performance. The JMCL aerogels delivered a water evaporation rate of 1.40 kg m-2h−1 and an efficiency of 91.20% under 1 sun illumination. In addition, the mechanical strength of JMCL aerogels is 437 times that of MXene/CNFs aerogels. The excellent salt resistance during 24h working and long-term solar vapor generation of up to 28 days were achieved. [Display omitted] Interfacial solar steam generation (ISSG) is considered to be an attractive technique to address the water shortage. However, developing a sustainable thermal management, salt rejection, and excellent mechanical strength ISSG device for long-term stability desalination is still a challenge. Herein, a biomass ISSG device with superb mechanical properties was prepared by introducing a luffa sponge as the skeleton and constructing the MXene/cellulose nanofibers (CNFs) aerogels via freeze-drying. The Janus MXene-decorated CNFs/luffa (JMCL) aerogels integrated the multifunction of fast water transport, good thermal management, and efficient photothermal conversion in a single module, to achieve high-efficiency desalination. 3D Janus structure endowed the JMCL aerogel with opposite wettability, which is feasible to construct the localized photothermal generation and self-floating. The mechanical strength of JMCL aerogels is 437 times that of MXene/CNFs aerogels. The JMCL aerogels delivered a water evaporation rate of 1.40 kg m-2h−1 and an efficiency of 91.20% under 1 sun illumination. The excellent salt resistance during 24 h working and long-term solar vapor generation of up to 28 days were achieved. The multifunctional JMCL aerogels with 3D Janus structure offer new insights for developing good durability and eco-friendly biopolymer-based steam generators.